2014
DOI: 10.1089/tmj.2013.0079
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of Remote, Telephone-Based Delivery of Cardiac Rehabilitation

Abstract: Objectives: Cardiac rehabilitation (CR) provides significant benefit for persons with cardiovascular disease. However, access to CR services may be limited by driving distance, costs, need for a driver, time away from work, or being a family primary caregiver. The primary aim of the project was to test the reach (i.e., patient and provider uptake), effectiveness (safety and clinical outcomes), and implementation (time and costs) of a remote telephone-based Phase 2 CR program. A secondary aim was to compare out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…21,22,39,40 To our knowledge, only 1 randomized study previously investigated the use of the Internet for cardiac rehabilitation remotely, 23 which comprised online chats between patients and nurses/dietitians, online educational resources, and financial incentives for participation. After 6 months, there was no difference in exercise capacity and the only parameter to improve compared with the control group was weight reduction.…”
Section: Summary Of the Experience Futurementioning
confidence: 99%
“…21,22,39,40 To our knowledge, only 1 randomized study previously investigated the use of the Internet for cardiac rehabilitation remotely, 23 which comprised online chats between patients and nurses/dietitians, online educational resources, and financial incentives for participation. After 6 months, there was no difference in exercise capacity and the only parameter to improve compared with the control group was weight reduction.…”
Section: Summary Of the Experience Futurementioning
confidence: 99%
“…This includes a study by Wakefield et.al, conducted in a Veteran population with a mean age of 63.7 ± 8.2 utilizing a remote, HBCR as well as periodic telephone calls. The study concluded that this model would not only bring CR services closer to patients, but noted participants were highly satisfied and had higher completion rates …”
Section: Hbcr With Telephonic Monitoringmentioning
confidence: 97%
“…The study concluded that this model would not only bring CR services closer to patients, but noted participants were highly satisfied and had higher completion rates. 32 Larger studies utilizing telephonic monitoring and mail contact with patients have shown to improve several coronary risk factors such as lipid profiles, activity, and smoking cessation, after acute myocardial infarction and the implementation of this could be useful for comprehensive CR. 33,34 In addition, in a study specifically following a CR program with telephone follow-ups found that the intervention resulted in a significantly improved Framingham score, total cholesterol, low-density lipoprotein cholesterol, and systolic blood pressure A randomized controlled trial also showed a significant benefit of digital health intervention when added to standard CR.…”
Section: Hbcr With Telephonic Monitoringmentioning
confidence: 99%
“…47,48 A recent study found that a remote CR program delivered to patients via telemedicine had higher completion rates and comparable costs compared with in-clinic programs. 49 Moreover, Milani and Lavie 19 utilized health professionals qualified to deliver CR services (ie, nurses, dietitians, health educators, and exercise physiologists and psychologists) to operate a CR program in the workplace. In this study, there was a significant improvement in cardiovascular risk profiles and reduction in health care expenditures.…”
Section: Opportunities For Workite Cr Programsmentioning
confidence: 99%